Event-related potentials discriminate familiar and unusual goal outcomes in 5-month-olds and adults - Michel, Christine (Developmental psychology, 2017)
Previous event-related potential (ERP) work has indicated that the neural processing of action sequences develops with age. Although adults and 9-month-olds use a semantic processing system, perceiving actions activates attentional processes in 7-month-olds. However, presenting a sequence of action context, action execution and action conclusion could challenge infants’ developing working memory capacities. A shortened stimulus presentation of a highly familiar action, presenting only the action conclusion of an eating action, may therefore enable semantic processing in even younger infants. The present study examined neural correlates of the processing of expected and unexpected action conclusions in adults and infants at 5 months of age. We analyzed ERP components reflecting semantic processing (N400), attentional processes (negative central in infants; P1, N2 in adults) and the infant positive slow wave (PSW), a marker of familiarity. In infants, the PSW was enhanced on left frontal channels in response to unexpected as compared to the expected outcomes. We did not find differences between conditions in ERP waves reflecting semantic processing or overt attentional mechanisms. In adults, in addition to differences in attentional processes on the P1 and the N2, an N400 occurred only in response to the unexpected action outcome, suggesting semantic processing taking place even without a complete action sequence being present. Results indicate that infants are already sensitive to differences in action outcomes, although the underlying mechanism which is based on familiarity is relatively rudimentary when contrasted with adults. This finding points toward different cognitive mechanisms being involved in action processing during development. (PsycINFO Database Record (c) 2017 APA, all rights reserved)